2015
DOI: 10.1007/s00384-015-2222-x
|View full text |Cite
|
Sign up to set email alerts
|

Histological and mechanical differences in the skin of patients with rectal prolapse

Abstract: Patients with prolapse have a higher concentration of elastin fibres in the skin, and these differences are quantitatively demonstrated through mechanical testing. This suggests that the aetiology may be a result of a dysfunction of elastin fibre assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…4,24 This notion is strengthened by the observations of higher rates of RP and POP among women with hereditary CTDs, such as Marfan and Ehlers-Danlos syndrome, 23,27 and alterations in elastin composition and metabolism. 28,29 Although CTD/myopathy was not significantly associated with RPR in our study, likely because of the small numbers, it is possible that some women had undiagnosed or subclinical connective tissue abnormalities that predisposed them to RP, POP, and RPR. Consistent with previously published findings, 22 we did not identify aging as an independent risk factor for RPR.…”
Section: Discussioncontrasting
confidence: 54%
“…4,24 This notion is strengthened by the observations of higher rates of RP and POP among women with hereditary CTDs, such as Marfan and Ehlers-Danlos syndrome, 23,27 and alterations in elastin composition and metabolism. 28,29 Although CTD/myopathy was not significantly associated with RPR in our study, likely because of the small numbers, it is possible that some women had undiagnosed or subclinical connective tissue abnormalities that predisposed them to RP, POP, and RPR. Consistent with previously published findings, 22 we did not identify aging as an independent risk factor for RPR.…”
Section: Discussioncontrasting
confidence: 54%
“…In 2015, Joshi et al [8] demonstrated a significant increase in the dermal elastic fibers in patients with RP compared to normal control patients.…”
Section: Dear Sirmentioning
confidence: 98%
“…Animal studies appear to support our hypothesis that, in part, fibulin deficiency or deficiency in elastin homeostasis may play a role in the development of prolapse [6,8,24]. Mice lacking lysyl oxidaselike 1 (LOXL-1), a key protein in the assembly of elastic fibres, do not deposit normal elastin fibres in the uterine tract postpartum and subsequently develop prolapse [5]. Drewes et al [8] and Budatha et al [22] showed that mice deficient in fibulin-5 also developed prolapse.…”
Section: Discussionmentioning
confidence: 71%